Factors Influencing Delayed Language Development among Children Aged 2-5 Years, Thabo District, Nongkhai Province - สกุลคู ฤดีมน (Journal of Health Science of Thailand, 2022)
This cross-sectional analysis study aimed to determine factors influencing language development among 210 children aged 2-5 years in Thabo district, Nongkhai province. Data were retrospectively collected using HOSxp program from October 2020 to April 2022. The data were analyzed using descriptive statistics and logistic multiple regression. Research results revealed that among children aged 2-5 years old, male children (ORadj=2.74, 95%CI: 1.31-5.69), children who have mothers with complications during pregnancy (ORadj=-36.94, 95%CI: 8.78-155.37) and children who access smart phone usage (ORadj=8.57, 95%CI: 2.17-33.86) were found to have significant delay in language development (p<0.05). Therefore, hospitals should provide campaign activities promoting family planning, raising awareness of qualified antenatal care, educating mothers and caregivers on development promotion and to perform vaccination as well as monitoring growth and development of children periodically.